2022
DOI: 10.3390/ijerph192416687
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Adaptation Strategies at a Local Scale: The Portuguese Case Study

Abstract: Coastal areas are home to more than 2 billion people around the globe and, as such, are especially vulnerable to climate change consequences. Climate change adaptation has proven to be more effective on a local scale, contributing to a bottom-up approach to the problems related to the changing climate. Portugal has approximately 2000 km of coastline, with 75% of the population living along the coast. Therefore, this research had the main objective of understanding adaptation processes at a local scale, using P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…They applied this model to a local government and for areas requiring improvement. Ramalho et al [18] investigated adaptation processes by local governments in Portugal and found that most local governments have developed and are implementing CCA strategies. The local governments that were studied are familiar with nature-based solutions but underestimate community-based adaptation.…”
Section: Financing Investment and Policy Formulation Based On Evidencementioning
confidence: 99%
“…They applied this model to a local government and for areas requiring improvement. Ramalho et al [18] investigated adaptation processes by local governments in Portugal and found that most local governments have developed and are implementing CCA strategies. The local governments that were studied are familiar with nature-based solutions but underestimate community-based adaptation.…”
Section: Financing Investment and Policy Formulation Based On Evidencementioning
confidence: 99%
“…According to Ramalho et al (2022), to address climate change and the consequences that derive from it, various authors have produced the concept of climate change adaptation, varying in their approach to the concept, which has resulted in various definitions. In fact, climate change adaptation has more success when applied at a local scale.…”
Section: Introductionmentioning
confidence: 99%